Lymphangioleiomyomatosis Diagnosis and Management: High-Resolution Chest Computed Tomography, Transbronchial Lung Biopsy, and Pleural Disease Management. An Official American Thoracic Society/Japanese Respiratory Society Clinical Practice Guideline - Gupta, Nishant; Finlay, Geraldine A.; Kotloff, Robert M.; Strange, Charlie; Wilson, Kevin C.; Young, Lisa R.; Taveira-DaSilva, Angelo M.; Johnson, Simon R.; Cottin, Vincent; Sahn, Steven A.; Ryu, Jay H.; Seyama, Kuniaki; et al. (American journal of respiratory and critical care medicine, 2017)
Recommendations regarding key aspects related to the diagnosis and pharmacological treatment of lymphangioleiomyomatosis (LAM) were recently published. We now provide additional recommendations regarding four specific questions related to the diagnosis of LAM and management of pneumothoraces in patients with LAM. Systematic reviews were performed and then discussed by a multidisciplinary panel. For each intervention, the panel considered its confidence in the estimated effects, the balance of desirable (i.e., benefits) and undesirable (i.e., harms and burdens) consequences, patient values and preferences, cost, and feasibility. Evidence-based recommendations were then formulated, written, and graded using the GRADE (Grading of Recommendations, Assessment, Development, and Evaluation) approach. For women who have cystic changes on high-resolution computed tomography of the chest characteristic of LAM, but who have no additional confirmatory features of LAM (i.e., clinical, radiologic, or serologic), the guideline panel made conditional recommendations against making a clinical diagnosis of LAM on the basis of the high-resolution computed tomography findings alone and for considering transbronchial lung biopsy as a diagnostic tool. The guideline panel also made conditional recommendations for offering pleurodesis after an initial pneumothorax rather than postponing the procedure until the first recurrence and against pleurodesis being used as a reason to exclude patients from lung transplantation. Evidence-based recommendations for the diagnosis and treatment of patients with LAM are provided. Frequent reassessment and updating will be needed.